Beyond the selfishness paradigm and "Organizational Citizenship": Work-related prosocial orientation and organizational democracy - Manfred Moldaschl; Wolfgang Weber (Technische Universität Chemnitz, Lehrstuhl für Innovationsforschung und nachhaltiges Ressourcenmanagement, 2011)
Many economists and psychologists refuse the idea that behaviour could be based on any other motives than selfish and hedonistic ones, at least in the context of economy, mainly based on a methodological premise, not so often on empirical research. The corresponding image of man that is inherent in exchange theories and expectancy-value theories has had a strong influence on research over the last decades. Despite this, concepts like Organizational Citizenship or Corporate Identity are in search of potentials concerning voluntary work engagement. And in the 'civil society' practical campaigns are looking for voluntary workers who help compensate socially disintegrative effects of capitalism without adjectives (Vaclac Klaus) and give people back meaning in self-determined work. These are two very different things which are deeply linked though. In this article we address this difference, criticize the concepts like Organizational Citizenship Behaviour (OCB), discuss concepts of prosocial work motivation and organizational democracy, and bind this all together in a conceptual alternative of mutualistic-prosocial work orientation.
Keywords: 330